Directory of ASTHRDP scholars aquatic (2007-2014), agriculture and natural resources (2013-2014). (Philippine Council for Agriculture, Forestry and Natural Resources and Development, Department of Science and Technology, 2015)
This Directory of Scholars, a sequel to the 2013 publication, presents the profile of 166 scholars, both degree and thesis in the aquatic sector from 2007 to 2014; and 18 scholars from the AFNR sector who graduated from 2013 to 2014. It aims to provide access to a pool of experts and more importantly, pave the way for catalyzing cooperative endeavors between and among government and private institutions, R&D centers of excellence; and industry stakeholders.